2019
DOI: 10.1002/jat.3768
|View full text |Cite
|
Sign up to set email alerts
|

Palmitate enhanced the cytotoxicity of ZnO nanomaterials possibly by promoting endoplasmic reticulum stress

Abstract: We recently synthesized ZnO nanomaterials (denoted as ZnO nanorods [NRs] and Mini‐NRs) and suggested that their cytotoxicity could be related with the activation of endoplasmic reticulum (ER) stress apoptosis. However, in a complex biological microenvironment, the ER stress‐apoptosis pathway could also be modulated by biological molecules, such as free fatty acids, leading to unpredicted biological effects. In this study, we investigated the combined toxicity of ZnO NRs/Mini‐NRs and palmitate (PA) to THP‐1 mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…However, the results from this study showed that Mxene QDs induced cytotoxicity but reduced the release of inflammatory mediators (Figure 6). A recent study obtained similar data that ZnO nanorods significantly induced cytotoxicity but reduced inflammatory mediator releases in THP‐1 macrophages (Chen et al, 2019). Thus, it is unlikely that Mxene QDs led to cytotoxicity by the induction of inflammatory responses.…”
Section: Discussionsupporting
confidence: 52%
“…However, the results from this study showed that Mxene QDs induced cytotoxicity but reduced the release of inflammatory mediators (Figure 6). A recent study obtained similar data that ZnO nanorods significantly induced cytotoxicity but reduced inflammatory mediator releases in THP‐1 macrophages (Chen et al, 2019). Thus, it is unlikely that Mxene QDs led to cytotoxicity by the induction of inflammatory responses.…”
Section: Discussionsupporting
confidence: 52%
“…Guo et al also showed that co‐exposure to SiO 2 NPs and oxidized low‐density lipoprotein (oxLDL) transformed macrophages into foam cells through ER stress‐mediated up‐regulation of scavenger receptors as well as inhibition of cholesterol efflux genes (Guo, Ma, et al, 2018). However, it should be noticed that the presence of lipids could influence NM‐induced macrophage foam cell formation, therefore it will be necessary to investigate the effects of NMs without additional supply of lipids (J. Chen et al, 2019; Q. Yang et al, 2019). Our group showed that MWCNTs promoted lipid accumulation in THP‐1 macrophages without the presence of lipids.…”
Section: Adverse Vascular Effects Of Nmsmentioning
confidence: 99%
“…5B-D). We previously found that the same type of ZnO NPs also induced excessive intracellular Zn ions but not oxidative stress (Luo et al 2018;Chen et al 2019;Cao et al 2022). Others have shown that stabilizing ZnO NPs with oleate reduced the intracellular concentrations of Zn ions and consequently alleviated NP-induced cytotoxicity to HepG2 and Caco-2 cells (Fang et al 2017).…”
Section: Discussionmentioning
confidence: 93%